Relación entre conductas prosociales y estilos de crianza en niños y adolescentes - Perez Egaña Peet, Cristina (2024)
Prosocial behaviors are essential for an integral wellbeing and the development of a cooperative society. Since parents are key figures in their children's behavior, the aim of the research was to find the relationship between prosocial behaviors and parenting styles in children and adolescents. To this end, a search was carried out in the Scopus, Scielo and Web of Science databases, considering the indications of the PRISMA guide by Page et al (2021). Ten papers evaluating the relationship between prosocial behaviors and parenting styles were recognized. Within the analysis of the studies, it was identified that the authoritative parenting style had a positive and statistically significant relationship with prosocial behaviors compared to other parenting styles. The main results, the participation of secondary variables and the practical implications of the findings were also discussed. Finally, the main limitations and recommendations of the work are indicated.